(untitled) (Research, Society and Development, 2021)
Bearing in mind the global impact of suicidal behavior and the relevance of developing effective prevention strategies, we sought to verify whether there was an association between the implementation of the September Yellow Campaign and eventual changes in suicide rates in a state in the northeast of Brazil, marked by a significant increase in suicide rates in the last 26 years, above the national average. To this end, data on mortality due to self-inflicted causes were collected in Ceará between the years 2009 and 2019. The data were analyzed using the Joinpoint Regression Program software in order to distinguish changes in trends through the identification of inflection points in the curve. mortality. There was no change in the trend in the frequency of suicides despite the implementation of the campaign in the general population, but there was an increase in the trend of suicides in the population between 15 and 29 years old, as well as stabilization among individuals aged 60 to 79 years after its onset. Publicizing the topic of suicide on social media in an unregulated manner during the September Yellow Campaign may justify the findings, being a hypothesis to be tested in future research.